Association of Soil Minerals and Organic Matter and Their Impact on pH Value - MARKUS ANDA (Jurnal Sumberdaya Lahan, 2008)
Clay and organic colloids are two factors that control major, if not all, chemical, physical and biological processes and soil properties but maintaining soil organic matter content under tropical conditions is difficult. The objectives of this review are to explore association between minerals and organic substances, mechanisms underlying the stabilization of soil organic matter, and their implication on pH0 of soil variable charge component. The modes of interaction in clay-humus complexes may occur through anion and ligand exchange to the crystal edges, cation or water bridge to basal surfaces, H-bonding to the siloxane or gibbsite sheetby van der Waals forces attraction (physical bonds), entrapment in crystal pores and intradomain regions, and adsorption in interlayer spaces. Organic matter preservation was related to amount of clay fraction, type of clay mineral present and aggregate formation. High preservation occurs in soils having high clay content, the presence of 2:1 minerals and amorphous minerals (allophane and imogolite), and a larger aggregate size. Current knowledge indicates that the mechanisms of soil organic matterstabilization are: (i) chemical recalcitrance involves elemental composition, the presence of functional groups, and molecular conformation of organic substances against decomposition by microbes and enzymes; (ii) chemical stabilization occurs through adsorption of functional groups to clay mineral surfaces and amorphous sesquioxides; (iii) physical protection involves organic substances being protected by clay fractions in soil pores, especially mesopres (2-50 nm) that limits the accessibility of microbes andenzymes. Soil organic matter is powerful in masking reactive mineral surfaces and generating soil negative charge, which is revealedby the low value of pH.